Thermodynamic and structural studies of 4-hydroxybenzaldehyde and simvastatin - Simões, Ricardo Alexandre Gravata, 1983- (2014)
Tese de doutoramento, Química (Química-Física), Universidade de Lisboa, Faculdade de Ciências, 2013